Separate is never equal : the story of Sylvia Mendez & her family's fight for desegregation - Tonatiuh, Duncan (2014)
"Years before the landmark U.S. Supreme Court ruling Brown v. Board of Education, Sylvia Mendez, an eight-year-old girl of Mexican and Puerto Rican heritage, played an instrumental role in Mendez v. Westminster, the landmark desegregation case of 1946 in California"--
Includes bibliographical references (page 39) and index.
Keywords: Mendez, Sylvia, -- 1936- -- Childhood and youth -- Juvenile literature; School integration -- United States -- Juvenile literature; Hispanic Americans -- Education -- Juvenile literature; Hispanic Americans -- Civil rights -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; JUVENILE NONFICTION / History / United States / 20th Century; JUVENILE NONFICTION / People & Places / United States / Hispanic & Latino; JUVENILE NONFICTION / Social Issues / Prejudice & Racism